STRATEGI CYBERSECURITY UNTUK PERLINDUNGAN DATA AKUNTANSI: KAJIAN LITERATUR SISTEMATIS 2021-2025 - IMAN SUYAKIN DAELI; Ririn Setia Ningsih; Karina Lolo Limbong; Jufri Darma (LAND JOURNAL, 2026)
The rapid digitalization of business processes has positioned accounting data as a strategic asset that is highly vulnerable to cyber threats such as ransomware, malware, and social engineering. Protecting this data is crucial not only to ensure operational continuity but also to maintain public trust and organizational accountability. This study aims to provide an in-depth review of relevant cybersecurity strategies for safeguarding accounting data, focusing on recent practices and technologies from 2021 to 2025. The research employed a Systematic Literature Review (SLR) approach by examining academic databases such as Scopus, Google Scholar, and SINTA, followed by content analysis and synthesized through a narrative synthesis method. The findings reveal that effective protection strategies emphasize a holistic and multilayered approach, including data encryption, role-based access control, multi-factor authentication, real-time system monitoring, and security audits. Beyond technical measures, employee training and awareness play a critical role in minimizing internal risks. In conclusion, the integration of advanced technologies with human factors and organizational policies significantly enhances the security of accounting data, ensuring data integrity while strengthening business resilience and sustainability in the digital era.